Application of Halal Certification by Indonesian Ulema Council on Electronic and Non-Consumption Products: Maslahah Perspective - Zarul Arifin; Hatoli Hatoli (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
The background of this research is indications from those who criticize the granting of halal certification on electronic and non-consumption products. At the same time, critics say that the granting of halal certification is only a religious capitalization, the mode of following the MUI trend, getting fees. Some say that this is a misperception. This research was conducted in August 2019. This study analyzes how MUI halal certification is in electronic and non-consumption products and how halal certification in electronic and non-consumption products is in perspective. This type of research is field research with an empirical sociological approach and descriptive qualitative research. Data collection techniques are literature, interviews, and documentation based on secondary sources from dictionaries, brochures, expert opinions, and religious leaders. Based on the study results, it is concluded that the application of MUI halal certification in electronic products is still voluntary, so there is no mandatory (obligation) from business actors to register their products in obtaining halal certification. The application of MUI halal certification in electronic and non-consumer products, firstly for refusing mudharat, must take precedence over taking little benefit. Secondly, for companies or producers, applying for halal certification aims to provide a sense of security and comfort in the community and increase the added value of their products. Finally, the existence of halal products, even though they are non-consumption, besides having benefits for people because they are more confident in the products used, also benefits the company and fulfills the provisions in the Act. Theoretically, this research's benefits are expected to provide reading sources and guidelines for developing science, especially in Islamic law related to halal certification by the Indonesian Ulema Council on electronic and non-consumer products. Practically, the results of this study are expected to provide clear information to the public regarding the application of halal certification by the Indonesian Ulema Council on electronic and non-consumption products.